The Influence of Msib (Independent Campus) Internships and Future Time Perspective on Student Work Readiness (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This study aims to determine the effect of internship variables and future time perspective on the work readiness of students of the Faculty of Economics and Business, National Development University "Veteran" East Java. This type of research is quantitative research using Smart PLS software analysis tools. The population in this study were 114 students and the sampling technique in this study used proportionate random sampling so that a total of 53 respondents were obtained. Data collection was carried out using interview, observation, and questionnaire distribution techniques. Data testing techniques include validity test, reliability test, R-Square, and bootstrapping hypothesis testing. Based on the results of the study, it can be concluded that MSIB internship has a positive and significant effect on the work readiness of students of the Faculty of Economics and Business, National Development University "Veteran" East Java. And future time perspective has a positive and significant effect on the work readiness of students of the Faculty of Economics and Business, National Development University "Veteran" East Java.